Biochemical Studies to Probe the Domain-Domain Communication Pathways in E. coli Prolyl-tRNA Synthetase - Schmit, Heidi (My University, 2013)
Aminoacyl-tRNA synthetases (AARSs) are a family of enzymes that catalyze the covalent attachment of amino acids to their corresponding transfer-RNA. These enzymes play critical roles in protein synthesis and viability. AARSs are comprised of many domains and each domain is responsible for carrying out a specific function for the proper attachment of correct amino acids to tRNAs. This study specifically focused on one enzyme of this family--prolyl-tRNA synthetases (ProRS), which attaches proline on to the tRNA[superscript]Pro. The purpose of this study was to identify the role of specific mutations in the inter-domain communication and catalytic activity of this enzyme.
Color poster with texts, charts, images, and tables.
Keywords: Escherichia coli; Catalytic RNA; Functional analysis; Interdomain communication; Mutagenesis; Posters